Anti-Money Laundering Under International Conventions - علي, غسان; مرتكوش, نمير (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Money laundering is one of the concepts that has emerged in aspects of organized crime. Which influences economic development. This prompted states to contract in the fight against money laundering, and also the fight against corruption. See also minimized the consequences of his crimes. Syria has legislated an arsenal of legal texts and ratified several international conventions in order to follow the international route. One of the greatest forms of crime in our society today, which affects security and economic prosperity, and therefore the international community to combat. By the conclusion of several international and regional conventions and treaties to combat this crime. Syria, where money laundering has recently spread, is clearly interested in putting an end to this phenomenon and combating it by promulgating several laws and creating specialized bodies aimed at controlling and combating this crime.